The Development of Cross-faculty/University Integrated Social Science Learning Model in the Faculty of Social Science, Universitas Negeri Medan - Nurmala Berutu; Muhammad Ridha Syafii Damanik; Maryatun Kabatiah (Randwick International of Education and Linguistics Science Journal, 2021)
The development of Industrial Revolution 4.0 has implications for all areas, including education. One of the emerging indicators is the application of the independent learning curriculum. Every human being has the right to learn wherever and whenever this is in accordance with the conceptual application of the curriculum. This research aims to develop an integrated social science learning model between faculties/universities that will be used to succeed in the independent learning curriculum at the Faculty of Social Sciences of Medan State University (FIS Unimed). The research is research and development in the field of education that uses data collection techniques using documentation studies, interviews, and workshops, the data sources used are lecturers and students of FIS Unimed. The research stage refers to the R&D research stage (Gall, Borg, & Gall,) [5], the stages performed include: 1) Research Planning 2) Subject Determination Model 3) Preparing Learning Tools for Model 4 Courses)) Input Course Content into LMS 5) Testing (simulation) and evaluation of Content 6) Follow-up improvements 7) Dissemination. The results of the analysis show that the development of model courses as part of the integrated social science learning model across faculties/universities in preparation for independent learning in FIS Unimed based on 4 criteria for learning models, namely 1)field-based learning in the Anthropology education Study Program 2) practice-based learning in the Geography Education Study Program 3) seminar-based learning in the Historical Education Study Program and 4) attitude-based learning in the Civic Education Study Program is very practical. The average practicality score of this model is based on students 'and lecturers' responses was 85, which categorized as very practical. Thus, the learning model course that has been developed will be used as a prototype for other courses at FIS Unimed in the framework of implementing the curriculum for independent learning in the future.